Time-varying minimum cost flow problems - Cai, X.; Sha, D.; Wong, C.K. (European journal of operational research, 2001)
In this paper, we study a minimum cost flow problem on a time-varying network. Let N( V, A, l, b, c r , c w ) be a network with an arc set A and a vertex set V. Each a∈ A is associated with three integer parameters: a positive transit time b( a, t), an arbitrary transit cost c r ( a, t), and a positive capacity limit l( a, t). Each x∈ V is associated with two integer parameters: a waiting cost c w ( x, t) and a vertex capacity l( x, t). All these parameters are functions of the discrete time t=0,1,2,… The objective is to find an optimal schedule to send a flow from the origin (the source vertex) to its destination (the sink vertex) with the minimum cost, subject to the constraint that the flow must arrive at the destination before a deadline T. Three versions of the problem are examined, which are classified depending on whether waiting at the intermediate vertices of the network is strictly prohibited, arbitrarily allowed, or bounded. Three algorithms with pseudopolynomial time complexity are proposed, which can find optimal solutions to the three versions of the problem, respectively.